Clinical Outcomes in Patients With Humeral Avulsion Glenohumeral Ligament Lesions in the Setting of Anterior Shoulder Instability: A Retrospective Comparative Study. Issue 2 (February 2022) - Davey, Martin S.; Hurley, Eoghan T.; Gaafar, Mohamed; Delaney, Ruth; Mullett, Hannan
Background: Humeral avulsion glenohumeral ligament (HAGL) lesions are often underreported but have been shown to occur in up to 10% of cases of anterior shoulder instability. Purpose: To compare clinical outcomes and recurrence rates of patients with HAGL lesions undergoing open stabilization for anterior shoulder instability versus a pair-matched control. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of all patients who underwent both arthroscopic and open stabilization procedures with a minimum 24-month follow-up was performed. Patients with HAGL lesions were pair-matched in a 1:6 ratio for age, sex, sport, level of preoperative play, and follow-up length with those without HAGL lesions who underwent arthroscopic Bankart repair alone. Return to play (RTP), the level of return, and the timing of return were assessed. In addition, recurrence, visual analog scale for pain (VAS), Subjective Shoulder Value (SSV), Rowe score, satisfaction, and whether they would undergo the same surgery again were compared. Results: A total of 15 patients with HAGL lesions who underwent shoulder stabilization procedures were included, with a mean age of 21.5 ± 4.1 years and mean follow-up of 53.5 ± 17.4 months, and were pair-matched to 90 patients without HAGL lesions. Overall, there was no significant difference in any of the clinical outcome scores (VAS, Rowe, SSV, satisfaction) used between the 2 groups (1.6 vs 1.7, P = .86; 83.4 vs 88.0, P = .06; 85.7 vs 87.2, P = .76; and 86.7% vs 94.5%, P = .26, respectively). In addition, there were no significant differences in terms of overall rates, levels, and timing of RTP between the 2 groups (93.3% vs 90.0%, P > .99; 80.0% vs 78.9%, P > .99; and 5.3 ± 2.2 vs 5.9 ± 2.9 months, P = .45, respectively). There was no significant difference in the rates of apprehension, subluxation, and recurrent instability between the HAGL and pair-matched control groups (26.7% vs 26.7%, P > .99; 6.7% vs 3.3%, P = .47; and 13.3% vs 6.7% months, P = .32, respectively). Conclusion: Patients with anterior shoulder instability undergoing surgical stabilization with open HAGL repair demonstrate excellent functional outcomes and high rates of RTP, with low rates of recurrence in the medium term compared with a control group without HAGL lesions who underwent arthroscopic Bankart repair alone.